Decomposition of HO on Pure and ZnO-Treated CoO/AlO Solids - G.A. El-Shobaky; N.H. Amin; N.M. Deraz; S.A. El-Molla (Adsorption Science & Technology)
The effects of Co 3 O 4 loading, precalcination temperature and ZnO treatment on the catalytic properties of the Co 3 O 4 /Al 2 O 3 system were investigated. The amounts of Co 3 O 4 were varied between 5.57 wt% and 32.0 wt% and the resulting solids subjected to heat treatment at temperatures in the range 400–600°C. The amounts of ZnO were varied between 0.36 wt% and 2.12 wt%. The results obtained indicated that ZnO treatment of Co 3 O 4 /Al 2 O 3 solids followed by precalcination at 400°C resulted in a progressive decrease in the particle size of the Co 3 O 4 crystallites in the resulting samples. The catalytic activity of such solids towards H 2 O 2 decomposition decreased progressively as the precalcination temperature employed was increased in the range 400–600°C. The relationship between the catalytic activity expressed as a plot of the reaction rate constant, k, versus the amount of Co 3 O 4 in the samples showed a progressive increase in the range 5.6–17.7 wt% followed by an abrupt increase when the extent of loading exceeded this limit. Treatment with ZnO effected a measurable increase (42%) in the specific surface area (S BET ) of the treated solids. However, such treatment also resulted in a considerable increase in the value of the reaction rate constant for the catalyzed reaction. Thus, the maximum increase in the value of k 20°C due to doping with 2.12 wt% ZnO attained a value of 543% while the corresponding increase in the value of the reaction rate constant per unit surface area, k̄ 20°C , was 331%. Precalcination at 400–600°C of Co 3 O 4 /Al 2 O 3 solids subjected to ZnO treatment did not modify the mechanism whereby the catalytically active constituents (surface cobalt species) were involved in the reaction although their concentration was altered without affecting their energetic nature.